Development of Prezi-Based Learning Media Assisted by Virtual Reality and Songs on Solar System Science Material - Huda, Muhammad Nurul; Sutikno, Putri Yanuarita (Jurnal Pijar Mipa, 2025)
Science learning in elementary schools often faces challenges in delivering abstract materials such as the solar system, especially due to the limited availability of interactive and interesting media. To overcome this, this study developed Prezi-based learning media assisted by virtual reality and songs as learning aids that are expected to improve students' understanding and learning experience. This study uses a development research method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The research stages include needs analysis, media design, product development, implementation in learning, and evaluation of the effectiveness of the media developed. Prezi media assisted by Virtual Reality and songs were tested through a series of validity and effectiveness tests to assess their quality in supporting learning. The results of expert validation showed that the media developed was categorized as very feasible, with a feasibility percentage reaching 92.85% from media experts and 93.75% from material experts. The validated media was then implemented in class 6 of SDN 6 Wulung with a population of 24 students. The results of the normality test showed a significance value above 0.05, which indicates that the data on all test results that had been carried out were normally distributed. There was an increase in learning scores as evidenced by the paired t-test value, which showed a value of 0.014 in small-scale classes and 0.000 in large-scale classes. In the N-Gain test conducted, the figure was 0.72, which is considered high in small-scale classes, and 0.69, which is considered moderate in large-scale classes. The use of Prezi and virtual reality technology combined with songs has been proven to be able to increase students' grades, interests, and involvement in learning. Thus, this media has the potential to be an innovative alternative in teaching science at the elementary school level. This study recommends further testing with a wider scope to ensure the sustainability and effectiveness of media use in various learning conditions.